Passive cooling energy systems: holistic SWOT analyses for achieving urban sustainability - Cheshmehzangi, Ali; Dawodu, Ayotunde (2020)
In urban sustainability, passive cooling energy systems are recognised as primary design factors that highlight efficient and performative buildings. In the literature, there is a gap in addressing these design systems in the form of strategies that holistically suggest sustainable energy systems, cleaner built environments, and urban sustainability. This study fills this gap by conducting comprehensive SWOT analysis of all major passive cooling energy systems. In doing so, the study highlights key implications from a multi-indicator perspective comprised of five primary indicators, ‘energy’, ‘policy’, ‘practice’, ‘health’, and ‘environment’. These indicators are significant for disciplines of sustainable energy systems and the built environment. Through an in-depth interdependency evaluation of these indicators, this study assesses the passive energy systems across three spatial levels of macro, meso, and micro. Finally, this paper provides a holistic overview of these sustainable energy systems from the policy and practice perspectives across the three spatial levels.